ANTIBACTERIAL ACTIVITY OF PEPTIDE-RICH EXTRACTS OBTAINED FROM FLOWERS OF Spondias purpurea L. AGAINST CLINICALLY RELEVANT SPECIES (REMUNOM, 2026)
Antimicrobial resistance (AMR) has intensified in recent decades, compromising the efficacy of available antibiotics and driving the search for new therapeutic alternatives. Plant-derived antimicrobial peptides (AMPs) stand out due to their structural diversity and effectiveness against bacterial species of clinical interest. Spondias purpurea L. is a species found in the Caatinga biome, notable for its fruit production and pharmacological activities, such as antimicrobial properties. However, there are no reports on the effects of its peptide extracts against pathogenic microorganisms. Therefore, this study aimed to obtain fractionated peptide extracts from S. purpurea flowers and evaluate their antibacterial activity against different strains of Staphylococcus aureus and Escherichia coli by using microdilution method. Peptide extraction was performed using phosphate buffer, followed by fractionation with ammonium sulfate precipitation (ranging between 50% and 90% saturation), resulting in the SpF-50-70% and SpF-70-90% fractions. Regardless of the tested concentration or bacterial species, no extract resulted in inhibition equal to or greater than 50%, preventing the determination of the IC₅₀. Regarding E. coli strains, both extracts inhibited growth in a concentration-dependent manner, with percentages ranging from 10% to 40%. This concentration-dependent effect was not observed in tests with S. aureus. The SpF-70-90% extract was more effective against the ATCC strain and MRSA, while the SpF-50-70% fraction demonstrated a greater inhibitory effect against the clinical isolate of S. aureus. In all treatments, the highest inhibition percentages were observed at the concentration of 200 µg/mL. The results suggest that flowers from S. purpurea constitute a potential source of bioactive peptides with antibacterial action, particularly against species of clinical interest. However, these findings represent a preliminary step in the prospection of isolated peptides. This reinforces the need for further purification, characterization, and functional evaluation studies of these molecules.